Overview of Merdeka Curriculum Implementation in Manggarai Primary Schools - Madu, Fransiska Jaiman; Mariana Jediut; Arnoldus Helmon (Jurnal Elementaria Edukasia, 2024)
The problem in this study is related to teachers' difficulties in implementing the Merdeka Curriculum. This study aims to describe the implementation of the Merdeka Curriculum in primary schools in Manggarai. The results showed that in general, the school's preparation was quite good as there were several things that had started to be done such as attending socialisation, training and workshops, attending in house trainings related to the implementation of the Merdeka Curriculum and holding good practice sharing activities with colleagues. The implementation in the field is manifested in activities such as, implementing the Independent Pathway Merdeka Curriculum, implementing a differentiated learning model system, following the independent pathway of change, gradually implementing target classes 1 and 4, in the 2023 school year, classes 1, 2, 4 and 5 while in the upcoming 2024 school year, the target is grades 1-6, and focusing on preparing the flow of learning objectives, studying the criteria for achieving learning objectives and so on. However, there are still so many obstacles that teachers face in the field.